Evaluation of steel desulphurization in the ladle during the utilization of briquetting fluxing agents for slags - Socha, Ladislav (Materiali in tehnologije, 2012)
This paper presents the experience obtained from plant experiments specialized in the usage of three types of fluxing agents for slags based on Alsub{2}Osub3. Proper experiments took place during the steel treatment by secondary metallurgy. The objective of the plant experiments was to assess the degree of steel desulphurization and its course. An assessment of the steel desulphurization with the help of basic parameters, such as the degree of desulphurization, the basicity, the content of easily reducible oxides, the proportion of CaO/Alsub{2}Osub3 and Mannesmann's index was made. At the same time the behaviour of the fluxing agents and the development of their dissolution in steelmaking slags were assessed.
Keywords: razžvepljanje jekla; steel desulphurization; žlindra; slag; fluxing agent; talilo; corundum; korund; secondary metallurgy; sekundarna metalurgija; steel; jeklo